Efecto de riego deficitario y agua salina sobre el rendimiento del cultivo de soja (Glycine max) - Iguago Arteaga, Jennifer Vanessa (2023)
The main objective of the research was to evaluate the effects of deficit irrigation and saline water on soybean yield. The treatments evaluated were: 100% irrigation requirements with fresh water (T1), 100% irrigation requirements with saline water (T2), 50% irrigation requirements alternating fresh water irrigation with saline water and fixed deficit irrigation (T3), 50% irrigation requirements with saline water and fixed deficit irrigation (T4), 50% irrigation requirements alternating fresh water irrigation with saline water and controlled deficit irrigation (T5) and 50% irrigation requirements with saline water and controlled deficit irrigation (T6). A randomized complete block design with six treatments, four replicates and 24 experimental units was used. The variables recorded were growth (plant height, root biomass, stem biomass and chlorophyll) and yield components (grains per pod, pods per plant, 100-seed weight, grain diameter, grain yield). The irrigation treatments evaluated did not significantly influence (p>0.05) the growth and yield components evaluated. However, numerically, the T2 treatment showed the lowest growth and yield averages, while T1 (100% fresh water) achieved the highest growth and yield. It is concluded that it is possible to use saline water from wells to irrigate soybeans, but it is advisable to mix it with fresh water to reduce the risk of salinization.